PROGRAM EVALUATION OF SRIWIJAYA STATE SPORT SCHOOL - Usra, Meirizal (Universitas Negeri Semarang, 2013)
This study aims to identify and analyze the performance of sports coaching, sportscoaching achievement, the feedback on activities, implementation of performancesports coaching activities, and the successfull sport achievement in Sriwijaya StateSport School (SONS). This study adopted a mixed method approach of qualitativeand quantitative research. The design for program evaluation is based on the CIPP(context, input, process and product) model. The results show that the establishmentof SONS is meant to develop the talents and achievements of student athleteswho are able to become high achievers. The school has not shown high achievementas expected as a special school for sport. The results show that the school has notbeen managed well, as a result the school high achievement has not been maximallymade. Therefore, it is suggested that the school should work closely with agenciessuch as the Provincial Office of Education who is responsible for managing andimplementing academic activities, Office of Youth and Sports who is responsible forproviding infrastructures and financial support, and National Committee for Sport(KONI) who is responsible for providing coaching and training.